Kanuni idare ilkesi - Akbulut, Emre (My University, 2013)
Kanunî idare ilkesi konulu doktora tez çalışmasında, Türkiye Cumhuriyeti Anayasası’nın “idarenin kuruluşunun ve görevlerinin kanunla düzenleneceğini” öngören 123. maddesi incelenmiştir. Çalışma dört bölümden oluşmaktadır: Birinci bölümde; idare hukukunda kanunîlik ilkesi ve kanunî idare ilkesinin Anayasal dayanakları incelenmiştir. İkinci ve üçüncü bölümlerde; Türkiye Cumhuriyeti Anayasası’nın 123. maddesinin anlamı ve kapsamı üzerinde durulmuştur. Bu çerçevede “idarenin kuruluşunun kanunla düzenleneceği” kuralının ne anlama geldiği ikinci bölümün, “idarenin görevlerinin ve yetkilerinin kanunla düzenleneceği” hükmünün ne anlama geldiği de üçüncü bölümün konusunu oluşturmaktadır. Üçüncü bölümde idarenin görevleri ve yetkileri idari faaliyet türlerine göre ele alınmış ve kanunîlik ilkesi idarenin düzenleyici işlemleri, birel işlemleri, eylemleri ve sözleşmeleri açısından ayrı ayrı incelenmiştir. Son bölümde ise Türk İdare Hukukunda kanunîlik ilkesi açısından sapma oluşturan veya bu yönde bir izlenim uyandıran müesseseler üzerinde durulmuş, sonrasında ilke için Anayasa’da bir istisna öngörülüp öngörülmediği sorusuna cevap bulunmaya çalışılmıştır.

This doctorate thesis the subject of which is intra legem and secundum legem attributes of administration dwells on the 123rd article of Turkish Constitution, which commands that “the structure and functions of the administration shall be regulated by law ” . The study is divided into four chapters: In the first chapter, the principle of legality in administrative law and the constitutional bases of intra legem and secundum legem attributes of administration are examined. In the second and third chapters, the meaning and enclosure of the 123rd article of Turkish Constitution are analysed. In this context, the meaning of the rule which states that the structure of the administration shall be regulated by law establishes the second chapter’s subject and the meaning of the rule which states that the functions and the powers of the administration shall be regulated by law establishes the third chapter’s subject. In the third chapter, the functions and the powers of the administration are treated according to the kinds of administrative activities and the principle of legality is examined separately in terms of the administration’s statutory acts, specific acts, actions and contracts. Finally, in the fourth chapter, it is focused on the subjects which breaches or seems like breaching as to the legality principle in Turkish Administrative Law and then it is tried to come up with an answer to the question whether any derogation is provided for the principle in the Constitution or not.
Keywords: Kamu Hukuku